Hyponatraemia in Acute Confusional States and Coma (Journal of Medicine, 2018)
Background: Though hyponatraemia is a common scenario in our daily clinical practice, the mortality and morbidity are very high without early detection and prompt treatment. Both under and over treatment of hyponatraemia may cause permanent brain damage. Proper and meticulous treatment may prevent development of permanent brain disorder. So, a study was carried out to see the prevalence of hyponatraemia in acute confusional states and coma. The effect of hyponatraemia on consciousness level was also observed.Materials & Methods: A cross sectional study.Results: A total number of sixty (60) cases with acute confusional state and coma were recruited in our study. Among 60 patients with acute confusional states including coma, 85% (51) patients were presented with hyponatraemia. In the study, mild, moderate and severe hyponatraemia were 20%, 13.33% and 51.67% respectively. Of the total study population, 31.67%, 33.33% and 35% presented with coma, stupor and drowsiness respectively. Severe hyponatraemia was found in 68.42% in comatose, 50% in stuporous and 38.1% in drowsy patients. 47.06% of hyponatraemic patients were noticed in several intracranial disorders. Hepatic encephalopathy, gastrointestinal disorders, chronic renal failure and ischemic heart disease comprised 13.73%, 11.76%, 9.80% and 5.89% respectively. Diabetic ketoacidosis and hypoglycaemic shock comprised 3. 92% each and congestive heart failure and acute respiratory distress syndrome comprised 1.96% each of hyponatraemic patients.Conclusions: Hyponatraemia is a common clinical problem in our day to day clinical practice. If neglected this may result in permanent brain malfunction which may be prevented with earlier detection and correction under meticulous supervision.J MEDICINE JUL 2018; 19 (2) : 110-113